Sonoridade narrativa como um processo temporalizante no cinema: a concepção de um roteiro relé - Rubia Gonzaga Pereira da Costa (2013)
This research aimed to demonstrate, by the means of a theoretical construction that incorporated concepts borrowed from Deleuze and Pierre Schaeffer, such as the 'movement-image', 'time-image', 'signage matter', 'relay-art', 'concrete music', 'things language', 'sound object', 'reduced listening', 'sonority', 'sound framework' and 'simulacrum'; and from the study of musical and audiovisual pieces; the sounds imageries/narrative properties, the understanding of perception as a relay in becoming; and to support the elaboration of a practical work designated as 'relay script': a screenplay, constituted by sound relays, in order to take shape as a future time-image animation film.